Managing democratic organizations. Volume I and II - Heller, Frank (Aldershot, 2000)
"A study of managing democratic organizations. It is part of the "Classic Research in Management" series, which presents, for each research programme, a set of papers which have had a major impact on subsequent research and thinking. In many cases these research reports and articles have appeared in books which are now out of print, or in early issues of journals which are not easily available to libraries. Each chosen article is reproduced in full. The volumes seek to enable a detailed analysis of the distinctive contribution of each research programme in its historical context. "